Optimizing Muscle Performance in Young Soccer Players: Exploring the Impact of Resisted Sprint Training and Its Relationship with Distance Covered - Aedo-Munoz, E; Brito, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Speed training with resisted sprints has been shown to positively affect neuromuscular performance in soccer players. Various loads, ranging from 10% to 120% of body mass, have demonstrated performance improvements across the spectrum. However, the impact of sprint distance with optimal load on these adaptive responses has yet to be thoroughly described. Objective. To analyze the influence of sprint distance in resisted sprints on muscle performance in young soccer players. Methods. This quantitative study utilized a pre-post experimental design. The sample consisted of 24 young soccer players (15.3 ± 0.68 years; 61.4 ± 7.08 kg; 1.60 ± 0.06 m) randomized into three groups (10, 20, and 30 m) and subjected to 12 sessions of resisted sprint training over six weeks. The volume was homogenized across groups, with a total distance of 120 m for each. The intervention’s effect was analyzed through performance in the isometric mid-thigh pull (IMTP), countermovement jump (CMJ), modified 505 agility test (505 m), and linear sprint tests. Differences were analyzed using a mixed ANOVA, incorporating a between-subjects factor (training group) and a within-subjects factor (pre- and post-intervention). Results. Time-dependent differences were observed in all groups for peak force (PF) (p < 0.001; η2p = 0.62), time to PF (TPF) (p < 0.001; η2p = 0.53), impulse at 50 (p < 0.001; η2p = 0.57), 100 (p < 0.001; η2p = 0.60), and 200 ms (p < 0.001; η2p = 0.67) in IMTP; jump height by impulse-momentum (p < 0.001; η2p = 0.64), rate of force development (p = 0.04; η2p = 0.14), yielding impulse (p < 0.001; η2p = 0.49), and concentric impulse (p = 0.01; η2p = 0.19) in CMJ; time (p < 0.001; η2p = 0.46) in 505 m; and average speed in linear sprint (p = 0.003; η2p = 0.36), with moderate to large effect sizes, regardless of the distance covered. No differences were observed for the interaction between the time* and group or between groups. Conclusion. Performance improvements were independent of the sprint distance, with no differences between training groups. Distances between 10 and 30 m may enhance muscle performance in young soccer players. © 2025 by the authors.